A COMPUTER SIMULATION STUDY OF NATURAL SILICATE MELTS. PART I: LOW PRESSURE PROPERTIES - Guillot B.; Sator N. (My University, 2007)
In implementing into a molecular dynamics simulation code a simple interionic potential developed to describe the nine component system K2O-Na2O-CaO-MgO-FeO-Fe2O3-A l2O3-TiO2-SiO2 (KNCMFATS), it has been possible to reproduce satisfactorily a number of thermodynamic, structural and transport properties of a representative set of natural silicate melts. An important conclusion reached in this study is the good transferability of the potential from felsic to ultramafic compositions although this transferability becomes less accurate with high silica contents (rhyolitic composition and beyond) and with very iron-rich silicates (e.g. fayalite). A key feature of the simulation is to make the link between macroscopic properties of the melt and its microscopic structure and dynamics. We thus obtain a relationship between the molar volume of the melt, the number of network modifiers and the oxygen coordination number. The simulation also allows one to quantify the coordination environment around the cations as function of the melt composition. Furthermore, the electrical conductivity of the high temperature liquid is investigated. © 2006 Elsevier Inc. All rights reserved.